Managing Ambiguity: Religious Intolerance and Policy in Indonesia - Alamsyah M Djafar (Jurnal Identitas, 2024)
This paper expands the existing knowledge on how actors construct frame ambiguity in policy formulation. This study elaborates on the discursive strategies used to manage ambiguity through arguing, framing, and blame avoidance, based on an analysis of case studies of policy formulation aimed at addressing religious intolerance in Indonesia. The findings demonstrate that actors utilize discursive strategies to achieve two main objectives: preserving majority values and maintaining dynamism and heterogeneity in response to evolving demands. The paper argues that ambiguity serves as a temporary mechanism to overcome impasses and differences in values and demands among actors. The findings of the study fill the gap in the limited number of studies that examine ambiguity in religious policy, especially regarding the relationship between religion and the state. Additionally, the findings provide insights for the application of analytical tools in understanding ambiguity and its role in promoting institutional change.